Surgical management of congenital meningo encephalocele in a new born jersey calf: A case report (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Surgical correction of congenital meningo encephalocele in a new born Jersey calf.Materials and methods: A day old jersey calf was presented with a swelling over frontal region, whioch was diagnosed as congenital cranial meningocele by findings of clinical examination, radiography and the same was corrected surgically under local infiltration anesthesia using lignocaine hydrochloride.Results: Recurrence was not observed in the calf and it was recovered uneventfullyConclusion: Congenital defects should be attended as earlier as possible so as to increase the chance of survivability.http://doi.org/10.5455/javar.2016.c143